Vulnerability of Dairy Based Livelihoods to Climate Variability and Change, A study of Western Ghat Region- Shivamogga, Karnataka - Radhakrishnan, Aparna (Indian Journal of Dairy Science, 2017)
Â This paper aims at assessing the vulnerability of Dairy Based Livelihoods to Climate Variability and Change in the Western Ghat ecosystem and for this purpose; data were aggregated to an overall Livelihood Vulnerability Index (LVI) to Climate Change underlying the principles of IPCC, using 28 indicators. Data were collected through Participatory Rural Appraisal and personal interviews from 180 randomly selected dairy farmers of three talukas of Shivamogga district complemented by thirty years of gridded weather data. The index score of dairy based livelihoods of Bhadravathi taluka was negative with overall value -3.58 with 45% farmers having high level of vulnerability.